PENGGUNAAN AUDIO LINGUAL METHOD DALAM MATA PELAJARAN BAHASA INGGRIS PADA SISWA MADRASAH ALIYAH NIZHAMIYAH PLOSO - rizqi fatichatul khusna (LPPM Universitas KH.A.Wahab Hasbullah Jombang, 2021)
This study aimed at explaining how is the implementation of Audio Lingual Method in teaching English. Audio Lingual method is defined as a method that emphasizes repetition of words to help students use communicative language . The writer used the descriptive qualitative research in conducting this study. The subject of the study was the tenth grade of MA Nizhamiyah Ploso, Jombang in the academic year of 2019/2020. The writer took one class to be used in this study consist of 15 students. In this study the writer used observation and interview to collect the data. The result of this study was Audio Lingual Method had positive roles in the teaching English. Keywords: Audio Lingual Method, English, students.